Eco-Maqāṣid in Climate Change Campaigns: From an Ecolinguistics Study to the Philosophy of Islamic Law - Haris, Arkin; Widodo, Aris; Tantri, Irma Dwi; Sarah, Siti (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2024)
This article aims to uncover ‘eco-maqāṣid’, an Islamic legal philosophy related to environmental awareness. Using a multimodality approach, the study begins by understanding the textual and visual meaning of climate change campaigns with Islamic themes on the @greenpeace.id Instagram account. The data were further explored through ecolinguistic studies to reveal The Stories We Live By, Ecological Philosophy (ecosophy), and Maqāṣid al-Sharī’ah. The findings show that the type of story constructed through the representation of the relationship between images and text is predominantly in the category of Salience, highlighting the importance of maqāṣid principles to environmental aspects. The principle of hifz al-nafs supports the promotion of environmental sustainability to protect Muslim health from the impacts of climate change. Hifz al-māl plays a role in the efforts of mitigation and adaptation to the threats of climate change to protect the assets and economic well-being of Muslim communities. Hifz al-nasl is related to the sustainable preservation of Islamic rituals, holidays, and cultural traditions. Meanwhile, hifz al-dīn is reflected in the endeavor to care for the environment as a religious duty manifested from Quranic verses and Hadith. Hifz al-‘aql resonates with strengthening environmental education through Ulama advice and Islamic ethics. Finally, all ḍarūriyyāt al-khams advocates for the protection of all elements in nature. This integration of maqāṣid into ecosophy illustrates how Islamic principles guide environmental management against climate change, creating a framework called ‘eco-maqāṣid’.